El Valor Nutritivo de los subproductos en Costa Rica. Composicion quimica, disponibilidad y uso. - Vargas-González, Emilio (Universidad de Costa Rica, 2013)
The nutritive value of rice by products in Costa Rica, Chemical composition, availability and use. By-products from the milling of rice, as obtained in Costa Rica, were examined for chemical composition and availability in the country. Data were taken from the CINA feed data base and from the literature. In Costa Rica, rice bran is a mixture of rice polishings and rice bran, without the broken rice and contain all the layers of the rice obtained in the milling operation of brushing the grain to polish the kernel. It may contain small quantity of hulls and germ of the rice. It must contain no less than 9% of crude protein and no more than 13% of crude fiber. The data show an availability of rice bran of 16.800 tons with an average protein content of 13.6% and 8.5% of crude fiber. The digestible energy swine was 3924 Kcal/kg of dry matter and 3340 Kcal/kg of dry matter of metabolizable energy for poultry. The brewers rice (polished and broken grain) and the rice hulls showed a chemical analysis typical for this type of products' It is suggested to control the marketing of rice bran mixtured with gro.rlá hulls which is illegal in CostaRica' It should be marketed as "bran with hulis".